A tangible interface for augmented reality visualisation in 4d echocardíography imaging of the left ventricle of the heart - Dias, J. M. S. (2021)
ln this work, we report a Tangible Augmented Reality system that can be applied to interactive visualization scenarios in the cardiology medical field, such as in the teaching of medical techniques or the recognition of organs. Moreover, it can be used for more detailed and natural interaction with virtual models of organs or other physiological structures of the human body. The system allows users to naturally interact with an augmented version of the previously referred models. The interaction with this model is made through a sensorless Tangible Interface, designated Magic Examiner, which aids the interaction and visualization tasks in the augmented environment.